The Conceptual Development of a Multifunctional Stepladder for Older People and Caregivers - Gan K.W.; Ng P.K.; Liew K.W.; Ng Y.J.; Yeow J.A. (MDPI, 2023)
elderly care; elderly population; health services; public health; quality of life; aged; Article; caregiver; exercise; health care; health service; human; independence; medical record; multifunctional stepladder; nursing home; physical mobility; quality of life; usability; caregiver; walker; wheelchair; Aged; Caregivers; Exercise; Humans; Nursing Homes; Walkers; Wheelchairs